The Language Varieties of Headline News in Analisa Newspaper - Nurmayana Nurmayana (Lembaga Komunikasi dan Informasi Dosen, 2022)
The perspective of systemic functional linguistics (SFL), the social context is constituted by three elements of ideology, culture and situation which are stacked up or stratified above language. The purpose of this study was to describe what is the varieties of language level that is used in the Headline News. The result found that The style of the language used in thatnewspaper is found obviously through its headlines. A headline’s main purpose is to quicklyand briefly draw attention to the news report under it. According to the restrictions to usecomplete sentences to save time and space as much as they can, the reporters inventedincomplete but striking sentences or phrases which make the headlines more dramatic. Theuse of puns, alliterations, distinctive grammar and the choice of emotive vocabularyaltogether make the headlines more memorable and effective.Keywords: Language Variety; Headine; Newspaper